Sexual satisfaction in nasopharyngeal carcinoma survivors: Rates and determinants. (October 2020) - McDowell, Lachlan; So, Nathaniel; Keshavarzi, Sareh; Xu, Wei; Rock, Kathy; Chan, Biu; Waldron, John; Bernstein, Lori J; Hui Huang, Shao; Giuliani, Meredith; Hope, Andrew; O'Sullivan, Brian; et al.
Abstract: Objectives: Sexual health problems have been identified as an unmet need in head and neck cancer (HNC) survivors. In particular, little is known about such outcomes in survivors of nasopharyngeal cancer (NPC). Materials and methods: A cross-sectional study of NPC survivors with ≥4y follow-up was undertaken. Sexual satisfaction was assessed using the optional "I am satisfied with my sex life" item of the FACT-H&N. Other patient-reported outcomes measures were also captured including fatigue (FACIT-F), HNC symptom burden (MDASI-HN), emotional distress (HADS) and frontal function (FrSBE). Univariate and multivariate analyses were performed to determine factors influencing sexual satisfaction. Results: The sexual satisfaction item was answered by 85/103 (83%) enrollees. Female ( p < 0.001) and non-partnered ( p = 0.0045) patients were more likely to abstain from answering. The distribution of responses were: "very much" (26%), "quite a bit" (21%), "somewhat" (20%), "a little bit" (13%) and "not at all" (20%). Sexual satisfaction was associated with multiple patient-reported measures on univariate analysis, including quality of life, fatigue, a priori selected HNC symptoms (pain, taste), emotional distress, frontal lobe function, body image and relationship strength. On multivariate analysis, only relationship strength and emotional distress remained significant. Sociodemographic factors (age, sex, marital status) and other selected orofacial toxicities were not significant. Conclusions: Nearly half (47%) of our sample reported being in the higher satisfaction range. While reassuring in the context of comparative population level data, a number of factors including toxicity, psychological and social factors were associated with sexual satisfaction responses. Prospective evaluation of this unmet need is required.